You-Tube and Instagram Content Development: Community Service to Empower and Promote Society - Hakim, Luqman Al; Supeni, Siti; Gunawan, Ifran; Ayudyanita, Diandra (International Journal of Community Service Learning, 2020)
The use of You-Tube and Instagram as Social Media is to inform the existence of Society. So, the role of society is to empower its potency and design content to promote the potency in order to be uploaded in those platforms. Community service program facilitates college students, as a part of society, to empower them and other members of society and create content based on its empowerment. The aim of the study is to describe the college students’ activities during their teaching on five programs (teaching English, Digital Content, Souvenirs, Local Culinary, and Healthy Lifestyle) in community service program as the content that would be uploaded in You-Tube and Instagram to promote Plesungan village. The subjects of the study are teenagers and mommies living at Plesungan village. The setting of the research is at Plesungan village, Karanganyar, Central Java, Indonesia. The research was carried out from 23 July 2020 up to 31 August 2020. The techniques in collecting the data are questionnaires, documentation (video recording and photograph), and observation. The technique analyzing the data used interactive analysis that contains data display, data reduction, and conclusion. Research findings show that the implementation of five training programs is successful viewed from the villagers’ participation and creativity, also the documentation in terms of videos and photos have been uploaded in The Instagram and You-Tube (the links attached).